New record for the army ant Labidus mars (Formicidae: Ecitoninae) in the Atlantic Rain Forest of São Paulo State, Brazil - Zara, Fernando José [UNESP]; Morini, Maria S. C.; Kato, Luciane M. [UNESP] (My University, 2003)
The occurrence of the army ant Labidus mars in Mogi das Cruzes (SP, Brazil) is recorded and includes additional information about the area, diet and foraging schedule of this rare army ant. This species of Ecitoninae was collected from two mature fruits of the Syagrus romanzoffiana (Arecaceae) and were probably in the foraging phase.
Keywords: Arecaceae; Ecitoninae; Formicidae; Invertebrata; Labidus mars; Syagrus; Syagrus romanzoffiana